2019
DOI: 10.3390/ijerph16224528
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Psychosocial Work Environmental Risk Factors for Back Injury among Healthcare Workers: Prospective Cohort Study

Abstract: The incidence of occupational back injury in the healthcare sector remains high despite decades of efforts to reduce such injuries. This prospective cohort study investigated the risk factors for back injury during patient transfer. Healthcare workers (n = 2080) from 314 departments at 17 hospitals in Denmark replied to repeated questionnaires sent every 14 days for one year. Using repeated-measures binomial logistic regression, controlling for education, work, lifestyle, and health, the odds for back injury (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
2
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 45 publications
3
71
2
5
Order By: Relevance
“…Results with a similar magnitude of excess risks of sickness absence were found for the combinations of job control and heavy physical work and strenuous postures, respectively. These results are in-line with research reviews and previous studies on how combinations of physical and psychosocial exposures among health and social care workers affect health, sickness absence, or disability [ 24 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 49 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results with a similar magnitude of excess risks of sickness absence were found for the combinations of job control and heavy physical work and strenuous postures, respectively. These results are in-line with research reviews and previous studies on how combinations of physical and psychosocial exposures among health and social care workers affect health, sickness absence, or disability [ 24 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 49 ].…”
Section: Discussionsupporting
confidence: 90%
“…Research reviews and individual studies among health and social care workers have shown that heavy lifting, twisting, and bending often are combined with urgent time pressure and low possibilities to determine the work pace, conditions known to increase the risk of musculoskeletal disorders, sickness absence, and disability [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. However, the effect of the combined exposure of psychosocial and physical risk factors on future health and sickness absence among health and care employees is rarely studied in terms of interaction effects; instead, the focus has been on single factors [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we investigated the potential dose-response relationships between subjective ratings of sleep quality (poor, moderate or good) at baseline and risk of a 1-point increase in LBP intensity on the visual analog scale (VAS) at follow-up. We have previously reported prospective associations between patient transfers and risk of back injury in this population [25].…”
Section: Methodsmentioning
confidence: 94%
“…In Western countries, injury rates are higher among health care workers (HCWs) than among workers in any other eld [1]. Being in patient care, HCWs are exposed to several occupational health hazards, such as viruses [2], ergonomic or physical hazards [3,4] and physical violence [5]. Threats and violence are in fact more frequently reported in Swedish health care than in other Swedish workplaces, and the percentage of those exposed has increased in the last years [6].…”
Section: Introductionmentioning
confidence: 99%